2012
DOI: 10.1002/jbmr.1793
|View full text |Cite
|
Sign up to set email alerts
|

Structure and strength of the distal radius in female patients with rheumatoid arthritis: A case-control study

Abstract: The purpose of this work was to investigate the volumetric bone mineral density (vBMD), bone microstructure, and mechanical indices of the distal radius in female patients with rheumatoid arthritis (RA). We report a cross-sectional study of 66 middle-aged female RA patients and 66 age-matched healthy females. Areal BMD (aBMD) of the hip, lumbar spine, and distal radius was measured by dual-energy X-ray absorptiometry (DXA). High-resolution peripheral quantitative computed tomography (HR-pQCT) was performed at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
33
3
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 47 publications
8
33
3
1
Order By: Relevance
“…Little is known about cortical bone changes in patients with RA apart from bone erosion and cortical bone loss in the phalangeal bones, as assessed by Dual-energy x-ray absorptiometry 41. Zhu and colleagues reported that Ct.Po is increased in women with compared to those without RA 35. In our study we did not find major differences in cortical density, Ct.Th or Ct.Po among RA[+], RA[−] and PsA subjects, suggesting that cortical bone changes are shared by various different inflammatory joint diseases.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Little is known about cortical bone changes in patients with RA apart from bone erosion and cortical bone loss in the phalangeal bones, as assessed by Dual-energy x-ray absorptiometry 41. Zhu and colleagues reported that Ct.Po is increased in women with compared to those without RA 35. In our study we did not find major differences in cortical density, Ct.Th or Ct.Po among RA[+], RA[−] and PsA subjects, suggesting that cortical bone changes are shared by various different inflammatory joint diseases.…”
Section: Discussioncontrasting
confidence: 57%
“…No study has been performed in PsA and only one study has been carried out in RA patients which focused on a subsegment of RA patients. Zhu and colleagues found that vBMD and BV/TV were decreased and trabecular inhomogeneity was increased in women with RA compared to those without RA 35. Although this study confirmed the notion that RA is associated with trabecular bone loss, the results can hardly be generalised based on the exclusive assessment of women, the lack of information about the autoantibody status and the fact that only a very few patients received biological drug therapy, which is now widely used for the treatment of RA and PsA patients in many countries.…”
Section: Discussionmentioning
confidence: 99%
“…vBMD and microstructure were measured at the distal radius of the non-dominant forearm using HR-pQCT (Scanco Medical AG, Bruettisellen, Switzerland) as described before1539. The participant’s forearm was fixed in a carbon fiber cast, and a dorsal-palmer projection image was obtained to define the tomographic scan region.…”
Section: Methodsmentioning
confidence: 99%
“…Trabecular thickness and separation were then derived from BV/TV and trabecular number using standard stereological relations. Our short-term HR-pQCT reproducibility, expressed as RMSCV, ranged from 0.38 to 1.03 % for density measures, from 0.28 to 1.10 % for geometric measures, and from 1.72 to 3.73 % for microstructural measures [22].…”
Section: Standard Analysismentioning
confidence: 99%